An Analysis Of Teachers’ Questioning Strategies During The English Class Interaction At SMP N 1 Juwana - Anggi Dwiyanti; Listyaning Sumardiyani; Jafar Sodiq (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The objectives of this study are to identify the types of teachers’ questioning strategies, to explain the types of questioning strategies that are mostly used, and to describe teachers' reasons for using questioning strategies based on Wajnryb's theory. The subjects of this study were two English teachers SMP N 1 Juwana who taught eighth-grade students. This research used a descriptive qualitative method and the data were collected and obtained from classroom observation, recording, and interview. Research findings show that both teachers used yes/no, short-answer, display, referential, and open-ended questions during the lesson, while imaginative questions never appeared during learning. Short-answer questions and display questions are types of questions that are mostly used by teachers. Research findings show the reason teachers use questioning strategies to provoke student responses and create a pleasant classroom atmosphere so that goals can be achieved. It was proven from classroom observations that students became more active when teachers used questioning strategies during teaching and learning activities.